A importância de pesquisas sobre teoria da produção para a construção - Vivan, André Luiz; Paliari, José Carlos (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
This article briefly discusses the need for innovative research on efforts to structure an explicit theory of production management in construction. It is a theoretical article that records the first considerations of the authors, in front of a research project in development by them. The main objective is to stimulate the discussion and development of innovative research for the body of knowledge in question, highlighting the importance of the subject for both the academic and practical spheres. The relevance of the article is due to two aspects: the expressive need for participation of national authors in the subject and the latent need for innovation and paradigm rupture in what concerns the development of an explicit theory of production management in construction.